Causes and timing of recurring subarctic Pacific hypoxia - Knudson, Karla P.; Ravelo, Ana C.; Aiello, Ivano W.; Knudson, Christina P.; Drake, Michelle K.; Sakamoto, Tatsuhiko (Science Advances, 2021)
Several North Pacific studies of the last deglaciation show hypoxia throughout the ocean margins and attribute this phenomenon to the effects of abrupt warming and meltwater inputs. Yet, because of the lack of long records spanning multiple glacial cycles and deglaciation events, it is unclear whether deoxygenation was a regular occurrence of warming events and whether deglaciation and/or other conditions promoted hypoxia throughout time. Here, subarctic Pacific laminated sediments from the past 1.2 million years demonstrate that hypoxic events recurred throughout the Pleistocene as episodes of highly productive phytoplankton growth and were generally associated with interglacial climates, high sea levels, and enhanced nitrate utilization—but not with deglaciations. We suggest that hypoxia was typically stimulated by high productivity from iron fertilization facilitated by redox-remobilized iron from flooded continental shelves.